Buddhist Ethics and Environmental Conservation in Thailand - Prasert, Somchai (Journal of Philosophy, Culture and Religion, 2024)
Purpose: The aim of the study was to analyze the Buddhist ethics and environmental conservation in Thailand. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Buddhist ethics in Thailand promote environmental conservation, emphasizing interconnectedness and compassion. This ethos encourages sustainable practices and fosters a sense of responsibility towards nature. Temples and monastic communities serve as hubs for environmental education and initiatives, yet challenges like urbanization and economic development threaten ecosystems. Integrating Buddhist principles into environmental policies is crucial for addressing these challenges effectively. Unique Contribution to Theory, Practice and Policy: Deep ecology, environmental virtue ethics & ecological economics may be used to anchor future studies on Buddhist ethics and environmental conservation sector. Promote community-based conservation initiatives grounded in Buddhist principles of compassion and interdependence. Integrate Buddhist environmental ethics into national and local policies on conservation and sustainable development.